Association between vitamin D, oestradiol and interferon-gamma in female patients with inactive systemic lupus erythematosus: A cross-sectional study. Issue 3 (March 2018) - Kokic, Visnja; Martinovic Kaliterna, Dusanka; Radic, Mislav; Tandara, Leida; Perkovic, Dijana
Objectives: To investigate possible associations between 25-hydroxyvitamin D3 (25(OH)D3 ), oestradiol (E2 ) and IFN-gamma (IFNγ) in female patients with inactive systemic lupus erythematosus (SLE). Methods: Female patients with inactive SLE and age-matched healthy controls were recruited into this cross-sectional study. Serum concentrations of 25(OH)D3, E2 and IFNγ were measured by radioimmunoassay with gamma-counters and enzyme-linked immunosorbent assay. Results: 36 patients and 37 controls were enrolled. In patients with SLE, the concentration of 25(OH)D3 was lower and E2 was higher compared with controls. In vitamin D deficient (i.e., 25(OH)D3 ≤20 ng/ml) patients, IFNγ was 150% higher compared with patients with 25(OH)D3 >20 ng/ml and controls. The concentration of E2 was higher in all patients compared with controls independently of the vitamin D level. A difference was found between patients and controls in the correlation of 25(OH)D3 with E2 and a positive correlation was found between E2 and IFNγ in all participants. Conclusions: Our results suggest that E2 may have a strong modulating effect on vitamin D function which is significant only at low concentration of E2 .